Cross-linked cellulose nanocrystal aerogels as viable bone tissue scaffolds. (15th March 2019) - Osorio, Daniel A.; Lee, Bryan E.J.; Kwiecien, Jacek M.; Wang, Xiaoyue; Shahid, Iflah; Hurley, Ariana L.; Cranston, Emily D.; Grandfield, Kathryn
Graphical abstract: Abstract: Chemically cross-linked cellulose nanocrystal (CNC) aerogels possess many properties beneficial for bone tissue scaffolding applications. CNCs were extracted using sulfuric acid or phosphoric acid, to produce CNCs with sulfate and phosphate half-ester surface groups, respectively. Hydrazone cross-linked aerogels fabricated from the two types of CNCs were investigated using scanning electron microscopy, X-ray micro-computed tomography, X-ray photoelectron spectroscopy, nitrogen sorption isotherms, and compression testing. CNC aerogels were evaluated  in vitro  with osteoblast-like Saos-2 cells and showed an increase in cell metabolism up to 7 days while alkaline phosphatase assays revealed that cells maintained their phenotype. All aerogels demonstrated hydroxyapatite growth over 14 days while submerged in simulated body fluid solution with a 0.1 M CaCl2 pre-treatment. Sulfated CNC aerogels slightly outperformed phosphated CNC aerogels in terms of compressive strength and long-term stability in liquid environments, and were implanted into the calvarian bone of adult male Long Evans rats. Compared to controls at 3 and 12 week time points, sulfated CNC aerogels showed increased bone volume fraction of 33% and 50%, respectively, compared to controls, and evidence of osteoconductivity. These results demonstrate that cross-linked CNC aerogels are flexible, porous and effectively facilitate bone growth after they are implanted in bone defects. Statement of Significance: Due to the potential complications associated with autografts, there is a need for synthetic bone tissue scaffolds. Here, we report a new naturally-based aerogel material for bone regeneration made solely from chemically cross-linked cellulose nanocrystals (CNC). These highly porous CNC aerogels were shown to promote the proliferation of bone-like cells and support the growth of hydroxyapatite on their surface in vitro. The first in vivo study on these materials was conducted in rats and showed their osteconductive properties and an increase in bone volume up to 50% compared to sham sites. This study demonstrates the potential of using functionalized cellulose nanocrystals as the basis for aerogel scaffolds for bone tissue engineering.